COVID-19 DALAM KAJIAN QAWAID FIQHIYAH - Nainunis Nainunis (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2021)
This study tries to assess the level of danger of covid-19 in the study of qawaid fiqhiyah. So that the level of vigilance is found based on the study of fiqh. There are several fiqhiyah principles that serve as basic guidelines in fostering human behavior in dealing with COVID-19, there are also some changes in the basic provisions (hukum ashal) to new provisions, which changes according to the level of the virus. The fiqhiyah rules that are relevant to this study are; 1) التيسير تجلب المشقة (difficulty can bring fast), which this rule describes the difficulties obtained from the process of spreading COVID-19 can abort obligations and change the basic provisions. 2) الضرورة تبيح المحظورات (the condition of the dharurat allows something that is forbidden), from the other side this rule also describes the same thing as the rule above, where dharurah is an excuse to fail an obligation and may do things that were originally prohibited. 3) ما أبيح للضرورة يقدر بقدرها (Something What is Allowed because dharurah is Measured According to the Level of ‘Endanger’), this rule describes the level of permissibility or legal relief that arises due to the spread of COVID-19 not absolutely, but it is adjusted to the level of the spread zone. 4), الضرر يزال (‘Endanger’ must be eliminated), in the spread of COVID-19, this rule becomes the basic guide for the new obligations, namely eliminating harm caused by the spread of COVID-19 by following health protocols. 5) قد نزلت منز لة الضرورة عامة كانت أو خاصة الحاجة (hajah;pretention Occasionally Occupies Emergency Positions either General or Special), this rule describes the desire with special criteria parallel to dharurah independently, such as hajah means, isolation of dharurah as a washilah to keep other people from being exposed.